Koordinasi Stakeholder Dalam Pengawasan Kapal Wisata Di Kota Pariaman - Limanik, Novia Rindi; Mubarak, Adil (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
This study aims to determine the coordination of stakeholders in the supervision of tourist boats in Pariaman City. The background of this research starts from the fact that there are still many deviations that occur that are not in accordance with those contained in the Standard Operating Procedures for Tourist Boats applicable in Pariaman City, as evidenced by the occurrence of tourist boat accidents in Pariaman City which caused the ship to sink and claimed lives. Coordination needs to be done because it involves various parties. The research method used is descriptive qualitative. For the selection of informants, the method was carried out by purposive sampling and followed by snowball sampling technique. In collecting data using interview techniques, observation and documentation. Data analysis is done by collecting data, reducing data, presenting data, and drawing conclusions. Then the validity of this data was tested by triangulation. This study uses coordination theory referring to the opinion of Malayu Hasibuan quoted from the Rahmeina Journal, there are four indicators of coordination, namely cooperation, communication, division of labor and discipline. The results of this study indicate that the coordination of stakeholders in the supervision of tourist boats in Pariaman City has been carried out but has not gone well. This is because of the four coordination indicators, two of which have not been implemented properly, namely communication and discipline indicators. Internal obstacles were also encountered, namely coordination evaluation meetings that were rarely carried out and external obstacles, namely the lack of awareness of the ship's crew to comply with regulations